Scope sensitivity tests for preference robustness: An empirical examination of economic expectations regarding the economic valuation of politices for reducing acidity in remote mountain lakes - Ian J. Bateman; Philip Cooper; Stavros Georgiou; Stale Navrud; Grey L. Poe; Richard Ready; Pere Riera; Mandy Ryan; Christian A. Vossler (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2004)
The paper introduces the reader to the contingent valuation method for monetary valuation of individuals preferences regarding changes to environmental goods. Approaches to the validity testing of results from such studies are discussed. These focus upon whether findings conform to prior expectations, in particular regarding whether valuations are sensitive to the size (or scope) of change being considered and whether they are invariant to changes in study design which are irrelevant from the perspective of economic theory. We apply such tests to a large sample study of two possible changes to the acidity levels of remote mountain lakes. Results suggest that robust values can be observed for a policy which would prevent further acidification of such lakes, but that values associated with measures to reduce acidity below present levels fail validity tests. Interestingly, values associated with preventing further acidification of lakes appear to be significantly lower for individuals who live further away from such lakes and there may even be a national component to this distance decay suggesting that those who live in the same country as the lakes in question hold higher values for their improvement.
Keywords: 330; acidity; Contingent valuation; distance decay; economic valuation; environmental preferences; Lakes; procedural invariance; scope sensitivity; Willingness to pay; Offenbarte Präferenzen; See; Gebirge; Schottland; Großbritannien